Formulation & Evaluation of Ketoconazole Antifungal Nanocream - Havale Vaishnavi Laxmikant; Dr.Satpute K.L; Waghmare R.S; Jadhav Payal Mahendra; Gandigude Sakshi Santoshrao; Hundekari Shivani Sadashiv (Asian Journal of Pharmaceutical Research and Development, 2025)
When it comes to delivering active ingredients to and through the skin for a variety of medicinal uses, nanoformulations have a certain position. These provide notable delivery advantages over coarse emulsions and are attractive, reasonably easy to manufacture, and reasonably inexpensive. A key technology opening the door for cutting-edge goods is nano technology. By using materials on a microscopic scale, nanotechnologies can give them new qualities not found in their bigger form. Further more, a vast range of consumer goods that are now available on the market and used in daily life can be altered by this technology. Nano cosmetics is one such fascinate in gareasince nano material can be used to createin nov active products. On the other hand, the manufacturing of UV filters for sunscreens in because they behave differently than larger forms, nanoforms may be more dangerous than larger ones. Numerous studies conducted in the last few decades have shown how successful these delivery technologies are. Furthermore, the creation of novel excipients with prospective applications in nanoformulations keeps opening up new possibilities for formulations with high distribution capacities and low toxicity and irritation. In order to assess the durability of nano-cream preparation, droplet size, electrical conductivity, drug content, pH, and rheological characteristics have all been investigated at various temperatures. Thus, the extraordinary behavior and features of nanomaterials have the potential to significantly alter both industry and human life. In addition to develop an effective, long lasting antifungal Nanocream and examine its antifungal activity and physico chemical properties.